PENINGKATAN PEMAHAMAN KONSEP.MATEMATIS DENGAN PENERAPAN MODEL PEMBELAJARAN ELPSA MELALUI MEDIA DART BOARD MATH - Diana Yonika Sari; Achi Rinaldi; Siska Andriani (IKIP Siliwangi, 2021)
The purpose of this study was to determine the ability to increase understanding of mathematical concepts of SMP Negeri 4 Natar students by applying the ELPSA learning model, ELPSA learning model through dart board math media and conventional learning models. The method in this study is a quantitative method using Quasy Experimental research and the research design used is Pretest-Posttest Control Group Design. The normality test used the Liliefors method, the homogeneity test used the Bartlett method. The N-Gain test is used to see the increase in the ability to understand mathematical concepts. Hypothesis testing using the one-way ANOVA test was continued using the Scheffe test (follow-up test) using a significant level of 5% or 0.05 and it can be concluded that increasing understanding of mathematical concepts applied by the ELPSA learning model through dart board math is better than increasing understanding of mathematical concepts who were treated with the ELPSA learning model and the conventional learning model.